Anion-controlled morphologies and photophysical features of organic microcrystals by solid-phase anion exchange reactions. Issue 12 (26th January 2016) - Shen, Chen; Yong, Guo-Ping; Zhang, Cong; Feng, Ya
Abstract : Anions play key roles in controlling the morphologies of organic microcrystals fabricated by simple and green solid-phase anion exchange reactions. Abstract : The ability to control the morphologies and photophysical properties of organic micro/nanomaterials is of special importance. The research reported herein demonstrates a solid phase anion exchange reaction can be used as simple, low cost and green approach to tailor the morphologies of boron-difluoride complex microcrystals. The great influence of anions on the morphologies of such organic microcrystals is also discovered. The changes in morphology induce distinctive changes in the photophysical properties. Compared to one- or three-dimensional morphologies, two-dimensional hexangular microflake, rhombic and rectangle microsheet morphologies reveal higher phosphorescent quantum yields and enhanced near-infrared absorptions, which should be attributed to the morphological anisotropy of two-dimensional microsheets, demonstrating morphology-sensitive photophysical features.